Revealing Selection in Breeding and Genetic Characteristics of Economically Important Traits of New Species of Apostichopus Japonicas Based on Genome Resequencing and GWAS Analysis - Guo, Chao; Li, Yuanxin; Xie, Jiahui; Han, Lingshu; Wang, Youquan; Zhang, Xianglei; Wu, YangLei; Song, Jian; Chang, Yaqing; Ding, Jun (Frontiers in Marine Science, 2022)
Apostichopus japonicas is an economically important species with high nutritional value. However, our knowledge of its genetic diversity and the genetic changes that occurred during its domestication or trait selection is quite limited. In this study, the whole genomes of 254 A. japonicas samples were resequenced. Analyses of the population genetic structure revealed that the genetic diversity of A. japonicas in the north of China is generally high, there was no difference in the population structure among the six cultured populations, and they were divided into two subpopulations together with AY-1 (new species). The results also showed that the genetic diversity of the AY-1 population was relatively low, the degree of linkage of alleles was high, and this population had been subjected to more positive selection. Based on Tajima’s D, FST analysis, and ROD analysis, the selected intervals and genes of the AY-1 population were identified, with some of the candidate intervals being related to an economically important trait and breeding target, namely, the number of parapodia. Gene Ontology analysis of the candidate genes revealed that the two subpopulations differed in their immune function, protein synthesis, decomposition, and transport, among others. Using GWAS, we identified 39 candidate genes for four economically important traits of A. japonicas, and we verified that those genes contained non-synonymous SNPs. Through this verification, BSL78_00022 and BSL78_00023 were found to be key genes for the number of parapodia in A. japonicas. Of these two genes, BSL78_00022 encodes a protein related to cell differentiation and proliferation, so it was assumed that three non-synonymous substitutions (Ser-Phe, Glu-Asp, and Ala-Val) in this gene are related to the changes in the number of parapodia. Meanwhile, the pleiotropic gene BSL78_04631, which is related to body weight and body wall weight, and promotes protein synthesis and cell growth, has a non-synonymous substitution (IlE-Val), which is assumed to be the reason for the difference in body weight and body wall weight of A. japonicas. These results provide a new perspective for explaining the genetic structure characteristics of A. japonicas and analyzing the selection and economically important traits in the breeding of new species.